Demystifying flexibility, exposing the algorithmic boss: a note on the first italian case classifying A (Food-delivery) Platform worker as an employee - Aloisi, Antonio (IE University, 2021)
In November 2020, the Palermo Tribunal reinstated a Glovo rider and reclassified him as a full-time, permanent employee, to be remunerated according to the applicable sectoral collective bargaining agreement (for the service sector), on the grounds that his autonomy was merely notional, since the platform could organize the execution of work and discipline noncompliance with rigorous instructions issued through the internal booking system. The judge ordered compensation for wage differentials and reimbursement for the unpaid time the worker spent waiting for orders. This dispatch is organized as follows. After a brief introduction, Section II describes the main facts underlying the legal dispute, as presented by the claimant and ascertained by the judge. Section III is aimed at disentangling the judge’s multi-layered reasoning. It covers four main topics: (i) the legal nature of the service rendered by the platform, (ii) the complementary techniques for classifying working relationships, (iii) the emergence of an adaptable notion of subordination, and (iv) the pervasive role played by management by algorithms. Section IV summarizes the key elements of the ruling and discusses its weaknesses.
Keywords: Platform work;Employment;COVID-19;Algorithm management;Gig economy;Subordination;European pillar of social rights; Platform work; Employment; COVID-19; Algorithm management; Gig economy; Subordination; European pillar of social rights